Short-term isokinetic training versus isotonic training: Effects on asymmetry in strength of thigh muscles - Golik-Peric, D.; Drapsin, M.; Obradovic, B.; Drid, P. (Journal of Human Kinetics, 2011)
The aim of this study was to investigate the effects of two training protocols on the isokinetic performance of athletes. The study was conducted in 38 athletes, (age 23.3 ± 3.6 years) participating in national level leagues of different sports, whose initial concentric hamstrings-to-quadriceps (conH/Q) torque ratio was lower than 0.5. During seasonal testing, an isokinetic measurement of knee extensors and flexors was performed at 60º/s. The athletes were divided into two groups. Nineteen athletes performed the isokinetic training protocol (IT) while the second group of 19 athletes followed the isotonic training protocol (RT). Both protocols lasted 4 weeks. After completing the training protocols, both groups underwent a final isokinetic testing. The isokinetic data revealed significant increases after training in measures of peak torque in both extensor and flexor muscle groups, in both the IT and RT study groups (p < 0.05). There were significant increases (p< 0.05) in conH/Q ratio in both groups after the implemented protocols, but greater in IT group. Consequently, applied IT protocol induced changes in working muscles, thereby restoring detected asymmetry to an acceptable balance more efficiently compared to RT protocol.